Understanding opportunities for urban forest expansion to inform goals: Working toward a virtuous cycle in New York City - Treglia, Michael L.; Piland, Natalia C.; Leu, Karen; Van Slooten, Alaina; Maxwell, Emily Nobel (Frontiers in Sustainable Cities, 2022)
Urban forests are critical infrastructure for mitigating environmental and social challenges cities face. Municipalities and non-governmental entities, among others, often set goals (e.g., tree planting or canopy targets) to support urban forests and their benefits. We develop the conceptual underpinnings for an analysis of where additional canopy can fit within the landscape, while considering factors that influence where trees can be planted, and canopy can grow (“practical canopy”). We apply this in New York City (NYC) to inform the setting of a canopy goal by the NYC Urban Forest Task Force (UFTF) for the NYC Urban Forest Agenda, which may trigger a virtuous cycle, or a positive feedback loop where people are mobilized to protect urban forest benefits that ultimately motivate people to commit to urban forest conservation. We further develop framing for a ‘priority canopy’ analysis to understand where urban forest expansion should be prioritized given more context (e.g., environmental hazards, local preferences), which can inform how expansion of the urban forest is achieved. We estimate an opportunity for 15,899 ha of new canopy in NYC given existing opportunities and constraints (practical canopy), which, if leveraged, could result in nearly doubling the canopy as of 2017 (17,253 ha). However, like existing canopy, practical canopy is not evenly distributed, in general, or across jurisdictions and land uses. Relying solely on areas identified as practical canopy to expand the urban forest would exacerbate these inequities. We discuss how the NYC UFTF established a feasible but ambitious goal of at least 30% canopy cover by 2035, which was informed by this analysis and guided by priorities of equity, health, and resilience. Achievement of this goal will ultimately require a combination of protecting and stewarding the existing resource, and leveraging opportunities for tree planting. Achieving a more equitable urban forest will also require identification of priority canopy, and, in cases, creation of new opportunities for tree planting and canopy expansion. Overall, the collaborative establishment of such goals based on local context can be instrumental in creating a virtuous cycle, moving conservation actors toward exercising influence and agency within the social ecological system.